Optimal cropping patterns and intertemporal groundwater usage under extraction constraints in Oklahoma’s panhandle - Lixia H. Lambert; Yiqing Yao; Lucia R. Levers (Agricultural Water Management)
Managing water resources is particularly important in the semi-arid Southern Great Plains of the United States. Surface water supply is limited compared to the extensive yet overly exploited groundwater resources of the Ogallala Aquifer. The region’s irrigators often encounter a reduced water table and tradeoffs between prolonging groundwater life and maximizing the profitability of irrigated agriculture. This research determines the optimal inter-temporal groundwater and land allocation to row crop production over time with varied ten-year water extraction rates, discount rates, and energy prices. A hydro-economic model is developed for Oklahoma’s Texas County, the state’s largest groundwater user. The model maximizes the Net Present Value (NPV) for producers, subject to resource constraints and a ten-year planning horizon. Results show higher water extraction rates significantly decrease the water table and overall profitability. With lower water extraction rates over ten years, dryland sorghum is a suitable replacement for irrigated maize. Higher energy costs did not show a significant influence on optimal cropping patterns and water usage paths when the water extraction rate is low. Results under different discount rates indicate that if producers put less weight on current costs and income, their total returns on irrigation water could increase over time with less water extraction.